2010
DOI: 10.1007/s10457-010-9329-4
|View full text |Cite
|
Sign up to set email alerts
|

Limits to recruitment of tall fescue plants in poplar silvopastoral systems of the Pampas, Argentina

Abstract: Forage production in silvopastoral systems of the Flooding Pampa is based on cool season grasses with a relatively asynchronous phenology regarding their accompanying deciduous trees. However, the productivity of cool season grasses in these systems is usually low. The hypothesis of this work is that the low productivity of cool season grasses is caused by tree litter constraining plant recruitment. Emergence and establishment (reproductive propagation), and tillering (vegetative propagation) patterns of tall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The original purpose of these plantations was timber production, yet they were never harvested, nor thinned or pruned. By the time of our study full canopy closure was observed (see Clavijo et al 2010). At the time of our study, 28 years after tall fescue was sown, this species was still abundant in the grassland stands (10-20% cover), although they were dominated by native species (62% cover, 71% species number) (Clavijo et al 2005).…”
Section: Study Area and Sitesmentioning
confidence: 81%
See 2 more Smart Citations
“…The original purpose of these plantations was timber production, yet they were never harvested, nor thinned or pruned. By the time of our study full canopy closure was observed (see Clavijo et al 2010). At the time of our study, 28 years after tall fescue was sown, this species was still abundant in the grassland stands (10-20% cover), although they were dominated by native species (62% cover, 71% species number) (Clavijo et al 2005).…”
Section: Study Area and Sitesmentioning
confidence: 81%
“…Moreover, light incidence is reduced and day temperatures tend to be lower under the canopy (Lin et al 2001 Syst (2011) 83:201-211 207 under which C3 species performance and fitness are relatively less affected (Jose et al 2004). After several years of interaction, the abundance of summer grasses in the understory of our stands is low whereas winter grasses dominate (Clavijo et al 2005(Clavijo et al , 2010. It is these differences in relative abundance, rather than changes in the seasonality of any functional group itself, what dictates the observed changes in the seasonal dynamics of productivity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Clavijo et al. () have documented that under trees of most forests and plantations (UC), understorey recruitment is limited by litter accumulated on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…In general, silvicultural practices such as thinning (which tends to open the canopy cover and reduce competition) promote an increase in diversity of plant species in the ground vegetation (French et al., ). Besides reducing competition, thinning may also reduce litter accumulation and soil acidification, since these processes intensify as canopy cover increases (Amiotti et al., ; Clavijo, Cornaglia, Gundel, Nordenstahl, & Jobbagy, ).…”
Section: Introductionmentioning
confidence: 99%